Optimasi Produksi Inokulan Cair Trichoderma harzianum Berbasis Molase - Reginawanti Hindersah; Wilhemina Rumahlewang; June A Putinella; A Marthin Kalay; Abraham Talahaturuson (Faculty of Agriculture, Pattimura University, 2015)
Trichoderma harzianum as a potential biological agent and are widely used to control diseases in various agricultural crops and plantations. This research goal of getting the best growth of Trichoderma harzianum on molasses-based liquid medium. The treatments tested was added 0.05%, 0.1% and 1% liquid pure culture of Trichoderma harzianum each in 500 ml of sterile liquid medium containing 5% molasses (v/v) and 5% commercial yeast (b / v), and incubated for five days. The results showed that Trichoderma harzianum growth with the highest number of spores occur if the molasses-based liquid medium supplemented with 1% Trichoderma harzianum.